Understanding Employee Well-Being: The Role of the Work Environment in Job Satisfaction at the Indian Postal Department in Gujarat (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
India Post is one of the leading government organizations in India and has been serving the communication needs of the public for many years. Over time, it has developed a strong brand image and earned a high level of trust among customers. Its extensive reach across the country is a key reason behind the Government’s decision to establish the India Post Payments Bank, with the aim of delivering financial services to even the most remote areas. This study seeks to examine the relationship between the work environment and job satisfaction among employees of IPPB. The research follows a descriptive design, with data collected through online structured questionnaires from randomly selected employees working in various post office branches across Gujarat. The sample includes both permanent IPPB employees and those deputed from the Department of Posts across different job roles. Statistical tools such as ANOVA and t-tests were used for data analysis. The findings reveal that the workplace does not exhibit bias in employee treatment; however, there is a need for greater motivation to foster a more challenging and engaging work environment.